The effect of employee performance assessment on job satisfaction at private university with work motivation as a mediator - Ika Raharja Salim; Fitri Aulia Rahma; Kendry Ayu Laksana; Gresi Agriany Silalahi; Anindita Millenika Sasmita (Enrichment : Journal of Management, 2023)
Technological developments are one of the factors of competition between companies, where in seeking competition, human resources can be assessed as an asset for the company. Increasing the capacity of human resources is then considered important so that companies can compete. This study aims to examine the effect of performance appraisal on job satisfaction mediated by work motivation. This study uses a quantitative method, where the respondents in this study are lecturers and staff at tertiary institutions. The targeted sample of respondents was 74, but managed to get 96 respondents. The questionnaire used in this study was adopted through previous research and then carried out validity and reliability. The results of this study indicate that the questionnaire used is valid and reliable, then for the effect test it is found that performance appraisal affects job satisfaction directly or through motivational mediation. This research has implications especially in the managerial field that it is important for companies to pay attention to the performance appraisal process to improve the quality and capacity of employees, and most importantly also increase employee motivation and job satisfaction.